Evolution of microstructure dependent corrosion properties of ultrafine AZ31 under conditions of extrusion with a forward backward oscillating die - Anna Dobkowska; Bogusława Adamczyk-Cieślak; Monika Chlewicka; Aleksandra Towarek; Aleksandra Zielińska; Milena Koralnik; Dariusz Kuc; Jarosław Mizera (Journal of Materials Research and Technology, 2022)
The present work aims to elucidate the role of microstructural changes induced by the extrusion with a forward backward oscillating die, thus verifying a novel approach to developing deformation methods for Mg-based alloys at ambient temperature. The main aim of this study was to show the process which enables the reduction of the hcp-structured AZ31 rods (40 mm in diameter) to the wires with diameters of 6 mm, 4 mm and 2 mm, without initial preheating of the billet. In contrary to the studies up to date, the significant microstructure refinement led to the decline in corrosion resistance of the wires with 6 mm and 4 mm diameters slightly relative to the original material. The highest extrusion ratio resulted in the formation of an ultrafine, equiaxed microstructure, which caused a tremendous corrosion resistance decrease. The significant decline in corrosion resistance of this alloy is a result of the highest number of HAGBs and is promoted by the accumulation of tangled dislocations. Summing up, the corrosion behaviors of the extruded alloys were mainly affected by the recrystallization stage that occurred during deformation, and not by the grain size alone.